2007
DOI: 10.1021/jp073610v
|View full text |Cite
|
Sign up to set email alerts
|

B3LYP and in Situ ATR-SEIRAS Study of the Infrared Behavior and Bonding Mode of Adsorbed Acetate Anions on Silver Thin-Film Electrodes

Abstract: The adsorption of acetate anions on silver thin-film electrodes has been studied by in situ infrared spectroscopy experiments and density functional theory calculations. Stable silver thin films were deposited either chemically or by argon sputtering on germanium and silicon substrates, respectively, and used as electrodes under internal total reflection conditions (ATR-SEIRAS) with a Kretschmann configuration. B3LYP harmonic IR frequencies of acetate species adsorbed with different geometries on Ag clusters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 39 publications
5
34
0
Order By: Relevance
“…[41][42][43] In the same way, we do not expect to have a significant effect of surface orientation on the vibrational bands of adsorbed 4-ABT and 4,4'-DMAB species. In addition, the small cluster size is not expected to significantly affect the calculated frequencies, as this is a local property.…”
Section: Synthesis Of Nanostructuressupporting
confidence: 50%
“…[41][42][43] In the same way, we do not expect to have a significant effect of surface orientation on the vibrational bands of adsorbed 4-ABT and 4,4'-DMAB species. In addition, the small cluster size is not expected to significantly affect the calculated frequencies, as this is a local property.…”
Section: Synthesis Of Nanostructuressupporting
confidence: 50%
“…As mentioned above, the ATR-SEIRAS experiments provide also information on the potential-dependent water-metal and water-adsorbate interactions [30,39,40]. In this respect, the in situ ATR-SEIRA spectra showed the existence of weak acetate-water interactions in agreement with bidentate bonding of adsorbed acetate and with the hydrophobic character of the methyl group [12,15,16,36,37]. In the case of the fluoroacetate anions, the ATR-SEIRA spectra show the existence of non-hydrogen bonded water molecules coexisting with the adsorbed anions, in an extent that depends on both the fluoracetate coverage and the number of fluorine atoms in the fluoroacetate anion [38].…”
Section: Introductionmentioning
confidence: 71%
“…This choice is based on the (1 1 1)-like character of the gold thinfilm electrodes used in this work, as well as on the absence of significant effects of the surface crystallographic orientation on both the experimental and calculated band frequencies for carboxylate anions adsorbed on metal electrodes [16,36,38]. On the other hand, previous studies on the adsorption of acetate at gold clusters showed that, when starting from unidentate bonding, the acetate was prone to go towards the cluster border or to desorb [36].…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations